Effective Use of Environmental Assets of Olexandria National Dendropark of NASU in the Environmental Network Concept of Ukraine - Galkin, S.; Kalashnikova, L.; Doiko, N.; Rubis, V.; Boiko, N. (Science and Innovation, 2024)
The article contains information about scientific research and engineering works carried out to create an ecological trail in Olexandria national deontological park of NASU in the concept of ecological network development in Ukraine. The objectives and criteria for developing the route of the ecological trail in Olexandria deontological park have been outlined. The new species to enrich the phytodiversity of the deontological park and the measures to optimize the habitat of introduced and native plant communities, rare and endangered species of plants and animals, as well as the expositional and collection sites have been listed; technical measures for the arrangement of ecological trail have been offered.